Estudio y prevalencia de dengue en personas adultas que acuden a consulta externa del Hospital Civil San Vicente de Paúl de la ciudad de Pasaje, determinado biometría hemática y pruebas serológicas inmunocromatográficas en el año 2014 - Aguilar Cuenca, José D. (2015)
Dengue is an infectious disease of viral cause, caused by a virus that is spread by the bite of an arthropod, is characterized by an acute febrile illness of limited duration (2-7 days), with severe malaise, headache, retro eye, muscle and joint pain, causing hematological abnormalities such as leukopenia, thrombocytopenia, increased hematocrit and even death. Aim of this work is to show the efficiency degree of serological tests and Biometry BLOOD immunochromatographic in patients with dengue. Methodology for the analysis of the results immunochromatographic method was employed quantitative method was applied using the equipment SYSMEX XS-1000i, which allowed the analysis to patients with dengue detected attending the Civil Hospital San Vicente Paul City Passage. Result: During the months of October, November and December 2014. It was shown that the number of dengue cases confirmed by IgM and IgG technical means is 34 patients out of 60 patients, equivalent to 56.66% which was significant for this research. The prevalence of dengue is given in the female population in a dominant 51.02% and 48.98% in the male population, predominantly between the ages of 25-30 years equals 31.67%, the predominant symptoms fever with 30%. As for the sharpest haematological abnormalities were leukopenia with 56.56%, with 35% lymphocytosis, thrombocytopenia with 58.33%. Conclusion: This work degree, both general and specific, objectives were achieved, the data obtained from research have much relevance for which we must prepare for health professionals to learn, understand and use these relationships to provide adequate diagnosis quickly, working together with the treating physicians.